Math, asked by vanshikadudeja9222, 8 months ago

5x-3=3x-5 by transforming method

Answers

Answered by divyamjan24
0

Answer:

hope this helps

Step-by-step explanation:

Hi!

That’s simple Algebra.

All you need is to pass all X terms in one side of the equation as it follows:

5x−3x=−5+3

2x=−2

Remember all mathematical operations pass with their opposite to the other side. As 2 is multiplying X, it divides our result in right. Then, we have:

x=−2/2

x=−1

Let’s prove the solution:

[(5)(−1)]−3=[(3)(−1)]−5

−5–3=−3–5

−8=−8

Yes, that’s true.

Similar questions